The Effect of Dragon Fruit Pudding on Hemoglobin Levels in Pregnant Women Anemia in the Independent Practice Area - Vittria Meilinda; Nia Darista (PT. Riset Press International, 2026)
Anemia in pregnant women remains a health concern in Sungai Penuh City, with 47 cases reported in 2024, contributing to a higher risk of preterm birth, low birth weight, and pregnancy complications. Red dragon fruit contains iron, vitamin C, folate, and antioxidants that play a role in hemoglobin synthesis. This study aimed to determine the effect of red dragon fruit pudding on hemoglobin levels among pregnant women with anemia at PMB Bd. Rika, S.Keb Sungai Penuh City in 2025. This research used a pre-experimental one group pre-test and post-test design. A total of 30 pregnant women with anemia were selected using total sampling. The study was conducted in November 2025. The intervention consisted of administering 250 grams per day of red dragon fruit pudding for 20 days. Hemoglobin levels were measured before and after intervention using a digital Hb test device and analyzed using the Wilcoxon test. The results showed an increase in the mean hemoglobin level from 10.49 g/dL before intervention to 11.7 g/dL after intervention, with a p-value of 0.000 (p < 0.05), indicating a significant effect of red dragon fruit pudding on improving hemoglobin levels among pregnant women with anemia. It is concluded that red dragon fruit pudding is effective as a non-pharmacological alternative for anemia management. Further studies are recommended to include a control group and longer follow-up for more comprehensive findings.